Integrated and free viral DNA in hamster tumors induced by BK virus. - Chenciner, N (1980)
BK virus (BKV)-induced tumors in hamsters were investigated for the presence of viral DNA by the blot-transfer hybridization technique. Several viral genomes per cell were found in tumor tissues and in their derived cell lines and clones. Most of the detected viral genomes were integrated into the cellular DNA, but some tumors also contained free viral DNA sequences. Integration patterns were different from each other, and many different integration sites were available on the cellular or on the viral DNA or on both. Typical features of integration patterns were found in ependymomas, which were the most frequent (72%) among BKV-induced tumors. Readily detectable viral DNA sequences were only found in neoplastic tissues, but traces of BKV DNA were also present in the apparently normal portion of the brain of an animal that had developed an ependymoma and in the brain (but not in the liver) of another animal 15 days after virus inoculation. A cell line and a single-cell clone derived from a tumor had hybridization patterns considerably simpler that the pattern of the original tumor, lacking several integrated viral genomes and all free viral sequences.